José-Luis García Barrientos (dir.), Análisis de la dramaturgia uruguaya actual. Madrid: Antígona, 2018. ISBN: 978-84-16923-78-6. 322 pp. - Migueláñez González, Daniel (Talía. Revista de estudios teatrales, 2020)
Reseña de Análisis de la dramaturgia uruguaya actual, José-Luis García Barrientos (dir.), Madrid, Antígona, 2018, 322 pp.